2015
DOI: 10.1016/j.jsv.2015.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-damping properties of a stiff and stable linear oscillator with a negative stiffness element

Abstract: A simple, stiff, statically and dynamically stable linear oscillator incorporating a negative stiffness element is used as a template to provide a generic theoretical basis for a novel vibration damping and isolation concept. This oscillator is designed to present the same overall static stiffness, the same mass and to use the same damping element as a reference classical linear SDoF oscillator. Thus, no increase of the structure mass or the viscous damping is needed, as in the case of a traditional linear iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
88
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(96 citation statements)
references
References 36 publications
(31 reference statements)
2
88
0
6
Order By: Relevance
“…A novel passive vibration isolation and damping concept, KDamper is proposed in Antoniadis et al [1] incorporating negative stiffness elements in the classical Tuned Mass Damper isolation system (TMD), which can exhibit extraordinary damping properties, without presenting the drawbacks of the traditional linear oscillator, or of the 'zero-stiffness' designs. This oscillator is designed to present the same overall (static) stiffness as a traditional reference original oscillator.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A novel passive vibration isolation and damping concept, KDamper is proposed in Antoniadis et al [1] incorporating negative stiffness elements in the classical Tuned Mass Damper isolation system (TMD), which can exhibit extraordinary damping properties, without presenting the drawbacks of the traditional linear oscillator, or of the 'zero-stiffness' designs. This oscillator is designed to present the same overall (static) stiffness as a traditional reference original oscillator.…”
Section: Introductionmentioning
confidence: 99%
“…Although the proposed oscillator incorporates a negative stiffness element, it is designed to be both statically and dynamically stable. Once such a system is designed according to the approach proposed in (Antoniadis et al, 2015 [1]), it is shown to exhibit an extraordinary damping behaviour. Figure 1 presents the basic layout of the fundamental vibration isolation and damping concepts to be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Combining the beneficial characteristics of both aforementioned typed of seismic isolation device, a novel passive vibration isolation and damping configuration is introduced, based on the KDamper concept introduced by Antoniadis et al [23]. The proposed device incorporates a negative stiffness element, which can exhibit extraordinary damping properties, without the drawbacks of TMDs or QZS oscillators.…”
Section: Introductionmentioning
confidence: 99%
“…However, the KDamper overcomes the sensitivity problems of TMDs as the tuning is mainly controlled by the negative stiffness element's parameters. Once such a system is designed according to the approach proposed in [23], it is shown to exhibit an extraordinary damping behaviour. A first approach to the implementation of the KDamper concept for the seismic isolation of a typical bridge can be found in [24].…”
Section: Introductionmentioning
confidence: 99%
“…The vibration of a uniform waveguide through the WFE technique was investigated in [32,33]. The WFE method has recently found applications in predicting the vibroacoustic and dynamic performance of composite panels and shells [34,35,36,37,38,39,40] , with pressurized shells [41,42] and complex periodic structures [43,44,45,46] having been investigated. The variability of acoustic transmission through layered structures [47,48], as well as wave steering effects in anisotropic composites [49] have been modelled through the same methodology .…”
Section: Introductionmentioning
confidence: 99%